Societal participation of individuals aged 55–64 years with and without chronic disease. (17th July 2018) - Scharn, Micky; van der Beek, Allard J; Suanet, Bianca; Huisman, Martijn; Boot, Cécile R L
Abstract: Background: It is unknown whether an increase in societal participation is important for individuals with a chronic disease. This study explores whether having paid work, volunteer activities or informal care giving differs for individuals with a chronic disease and those without. Methods: Respondents ( n = 1779) aged 55–64 years who participated in the Longitudinal Ageing Study Amsterdam in 2002/2003 or 2012/2013 were included. We tested differences in (combinations of) performing paid work, volunteer activities or informal care giving between participants with and without a chronic disease by regression analyses, while taking into account sociodemographic confounders and effect modification by year. Results: Having a chronic disease was associated with having paid work in 2002/2003 (OR: 0.5; 95% CI: 04–0.7), but not in 2012/2013 (OR: 0.7; 95% CI: 0.4–1.1). Work participation of participants with (OR: 1.5; 95% CI: 1.0–2.2) and without a chronic disease (OR: 2.3; 95% CI: 1.3–3.9) increased in 2012/2013. Participants with a chronic disease are more likely to participate in volunteer activities than paid work. No statistically significant associations were found between having a chronic disease and informal care giving. Conclusion: Participation in paid work differs between individuals aged 55–64 years with a chronic disease and those without, but participation in informal care giving did not. Individuals with a chronic disease are more likely to participate in volunteer activities than paid work. Future research should focus on differences in societal participation within heterogeneous group of individuals with a chronic disease, since differences may be present in subgroups with specific chronic diseases.